Evolutionary Approaches to Combat Antibiotic Resistance in Microbes - Sunita Rani; Priyanka; Sonam Sharma; Tinku; Rajesh Kumar; Vinay Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Antibiotics are one of the most important discoveries yet on earth. However, the rise of antibiotic resistance among microorganisms has lowered their potency of treatment for diseases which is now becoming life-threatening to patients. In this context, the present review discusses the reason for the development of resistance among bacteria through their mechanisms and evolutionary approaches to address this issue. Quorum sensing inhibition, bacteriocins, nano therapy, phage therapy, and essential oils have been discussed in the present work.
Keywords: Antibiotics Resistance; Nano Therapy; Quorum Sensing; Bacteriocins